Evaluation of protein sparing effect in Nile tilapia Oreochromis niloticus fed with organic selenium supplemented diet - Christian Ernsz Pattipeilohy; Muhammad Agus Suprayudi; Mia Setiawati; Julie Ekasari (Jurnal Akuakultur Indonesia)
ABSTRACT